A Networked Game Theoretic Model for Evaluating Resilience in Megaprojects: Integrating Stakeholder Interactions and Lifecycle Adaptability - Zhang, Hongsi; Jiang, Shukai; Lin, Xingwu; Yu, Xiang; Zheng, Wenjiang (Systems (Basel), 2025)
Megaprojects are complex systems comprising interdependent subsystems and diverse stakeholders, each contributing to the project’s resilience and long-term outcomes. Traditional methods for assigning stakeholder influence often assume that stakeholders operate independently when evaluating subsystem resilience. However, these approaches overlook the intricate dynamics—such as competition and collaboration—that frequently characterize stakeholder interactions in megaprojects. This study addresses this gap by introducing a novel framework based on game theory and network analysis to assess megaproject resilience. The model incorporates both stakeholder interactions and subsystem interdependencies, using a networked game approach to dynamically allocate stakeholder weights. These weights reflect cooperative and conflicting relationships among stakeholders. The framework optimizes a stakeholder’s utility function by balancing marginal benefits, costs, and interaction effects, ensuring rational and adaptive weight distribution. The resulting solution represents a unique Nash equilibrium, identified as the optimal configuration for stakeholder influence. To validate the framework, the study applies it to the Jakarta–Bandung High-Speed Railway (JBHSR) megaproject, demonstrating its capacity to integrate theoretical rigor with practical application. Through mathematical proofs and simulations, the research explores how model parameters influence two critical solution properties: order consistency and stability. Comparative analysis with established methods, such as the Analytic Hierarchy Process (AHP) and simple averaging, highlights the proposed model’s superior ability to capture stakeholder dynamics and adapt to the evolving nature of megaprojects throughout their lifecycle. The findings emphasize the model’s utility in delivering more nuanced resilience evaluations by accounting for stakeholder roles, relationships, and contributions. Specifically, this framework advances theory by merging network analysis with game theory to capture dynamic stakeholder influences, while offering practitioners a real-time mechanism to manage and optimize stakeholder interactions for improved resilience across the entire megaproject lifecycle. Its adaptability to full lifecycle assessments makes it a robust and scalable tool for managing resilience in large-scale infrastructure projects, offering valuable insights for both practitioners and researchers.